Common sense on mutual funds - Bogle, John C. (J. Wiley & Sons, 2010)
"Written in a straightforward and accessible style, this reliable resource examines the fundamentals of mutual fund investing in today's turbulent market environment and offers timeless advice in building an investment portfolio. Along the way, Bogle shows you how simplicity and common sense invariably trump costly complexity, and how a low cost, broadly diversified portfolio is virtually assured of outperforming the vast majority of Wall Street professionals over the long-term"--Resource description page.
Includes bibliographical references (pages 607-611) and index. - Print version record
Keywords: Mutual funds; Investments; Investissements